Function diversity of the expansin subfamily genes in Populus tomentosa - Zhang, Junkang; Zhao, Han; Zhang, Hao; Yang, Mengjia; Chen, Yuxi; Xu, Jichen (Frontiers in Plant Science, 2026)
Expansins are crucial components in plant cell walls and are classified into four subfamilies based on their sequences. To investigate their function differentiation in plant growth and stress resistance, four expansin subfamily genes—PtoEXPA8, PtoEXPB3, PtoEXLA2, and PtoEXLB1—were cloned from Populus tomentosa Carr. TC1521. Their sequence and structure exhibited typical subfamily characteristics. They were individually introduced in tobacco plants and made different contributions to the plants’ performances. Compared to wild-type plants, the PtoEXPA8 overexpressing lines increased the leaf area, and PtoEXPB3 facilitated floral organ development and earlier flowering and increased flower diameter. PtoEXLA2 increased plant height but reduced flower diameter and 1000-seeds weight. Finally, PtoEXLB1 increased plant height and decreased flower diameter. Under heat stress conditions, compared to the wild-type plants, the PtoEXPA8 overexpressing plants performed the best, while the other three genes barely contributed to heat resistance. The results indicate that the expansin subfamily genes underwent significant function differentiation, playing distinct roles in plant growth and stress resistance in poplar.